Cooperative Education: Soft Skills and Complementary Supervision in Field Immersion Engender Lifelong Learning - Carreon, Jonathan Rante (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
The transglobal nature of business transactions assumes skills that have been honed by active theoretical and practical immersions, and remained in the learners’ repertoire of skills through constant, guided practice provided by the concerted effort of the academe and the affiliated business or service industry partners, where the students were sent to undergo cooperative education training. The current study has a three-fold purpose: (1) examine which soft skills were developed during the cooperative education training process, (2) analyze which of these soft skills most likely engender lifelong learning, and (3) investigate the potential influence of the complementary supervision implemented for the training. Using a questionnaire, the perspectives of the 27 training supervisors (TS), 12 academic supervisors (AS), and 58 student trainees on the delivery of the complementary cooperative education training were gathered, followed by a semi-structured interview among volunteer participants. The findings from the surveys revealed that lifelong learning skills of students could be enhanced by developing their Life and Career Skills (e.g. Productivity & Accountability, Leadership & Responsibility, and Flexibility & Adaptability), and Learning and Innovation Skills (Collaboration, and Creativity & Innovation). These findings were confirmed in the responses of three groups of participants in the semi-structured interview. Implications of the study particularly on the enhancement of students’ lifelong learning skills were drawn